2019
DOI: 10.3390/informatics6040044
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Engagement Study for a Serious Virtual Reality Game of Lunar Exploration Missions

Abstract: Virtual reality (VR) technologies have opened new possibilities for creating engaging educational games. This paper presents a serious VR game that immerses players into the activities of lunar exploration missions in a virtual environment. We designed and implemented the VR game with the goal of increasing players’ interest in space science. The game motivates players to learn more about historical facts of space missions that astronauts performed on the Moon in the 1970s. We studied usability and engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…An important element connected to trainee engagement with the subject matter (specifically, emotional, thought awareness, and memory recall activities) was the affordance of privacy in a group setting provided by the VR headset. Existing research into the use of VR in education and training has shown the benefits of immersive VR over 2D screen delivery in areas of increased relaxation and arousal, motivation, engagement, and interest [34,[66][67][68]. Although future research is required to validate the outcomes for PE platform in direct comparison to a screen-delivered training tool, it seems unlikely that trainees would feel an equivalent sense of presence, privacy, and engagement in a room and training setting of 20 trainees.…”
Section: Engagement and User Acceptance Of A Novel Training Solutionmentioning
confidence: 99%
“…An important element connected to trainee engagement with the subject matter (specifically, emotional, thought awareness, and memory recall activities) was the affordance of privacy in a group setting provided by the VR headset. Existing research into the use of VR in education and training has shown the benefits of immersive VR over 2D screen delivery in areas of increased relaxation and arousal, motivation, engagement, and interest [34,[66][67][68]. Although future research is required to validate the outcomes for PE platform in direct comparison to a screen-delivered training tool, it seems unlikely that trainees would feel an equivalent sense of presence, privacy, and engagement in a room and training setting of 20 trainees.…”
Section: Engagement and User Acceptance Of A Novel Training Solutionmentioning
confidence: 99%
“…The use of virtual reality opens up very wide opportunities for education, thanks to interactivity, creativity and deep involvement, it can significantly motivate students to learn. Numerous studies have shown that the use of educational games based on virtual reality has a positive impact on the level of student involvement and the quality of their learning (Cao et al, 2019;Cheng et al, 2015;Lim et al, 2017). The degree of student involvement has a strong correlation with learning outcomes in a computer-based learning environment (Tempelaar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Creating a serious game about a mission to the moon and evaluating the use of Virtual Reality (VR) with respect to usability and engagement are the focus of Lizhou Cao, Chao Peng, and Jeffrey T. Hansberger's contribution [3]. In this work, they design and implement a serious VR game that immerses players into activities of lunar exploration missions in a virtual environment.…”
Section: Games As Teaching Toolsmentioning
confidence: 99%